Japan Children's Cancer Group: International collaborations and plans - Yasuhiro Okamoto (Elsevier, 2020)
Japan Children's Cancer Group (JCCG) is the only national clinical research group for childhood cancer in Japan, which was established in December 2014. In this paper, the JCCG describes its efforts in Japan and Asia and shares its current goals for enhancing the effective treatment of childhood cancer. International collaborative research is necessary for expeditious meaningful clinical outcomes because childhood cancers are relatively rare. The purpose of JCCG's international committee is to facilitate smooth international cooperation based on the JCCG Constitution to support the exchange of domestic and foreign research results, strengthen international cooperation in paediatric cancer treatments. At this moment, two clinical trials are ongoing, including JPLT4: PHITT for pediatric hepatic tumor and ASIA DS-ALL 2016 for acute lymphoblastic leukaemia in children with Down syndrome. Other than JCCG activity, several activities will be introduced including Japan Heart. Finally, the Global Initiative for Childhood Cancer was launched with a goal of at least a 60% survival rate for children with cancer by 2030. The international committee of JCCG is one of the members of leading this activity in Japan. It began working with the International Committee of The Japanese Society of Pediatric Hematology/Oncology to participate in this effort on behalf of paediatric cancer care in Japan.